Examining a model of tourist loyalty in homestay tourism village balkondes Borobudur area in the new normal period - Ivo Novitaningtyas; Dian Marlina Verawati; Andhatu Achsa (Jurnal Manajemen dan Pemasaran Jasa, 2021)
Tourism business is affected by Pandemic Covid-19. Tourist loyalty was proven as an important key for the recovery of tourism business, including homestays in tourism villages. Therefore, this study aims to examine the model of tourist loyalty in homestays tourism village Balkondes Borobudur area in the new normal period. The quantitative study was conducted by developing a questionnaire to get primary data from 100 respondents who have stayed in a homestay tourism village Balkondes Borobudur area in the new normal period more than once as samples. Data were analyzed by Structural Equation Model (SEM) with AMOS, and Sobel Test to examine the mediation effect. The results show that service quality and image has a positive and significant effect on tourist satisfaction, tourist trust, and tourist loyalty. Moreover, tourist satisfaction and tourist trust proved that these variables mediate the relationship between service quality and tourist loyalty, and between image and tourist loyalty. The results have implications for the homestay tourism village manager to improve the quality of services based on health protocols and CHSE, communicate a positive image to guests through a marketing communication mix, to increase guest satisfaction and trust. Thus, it is hoped that the guests who have stayed will become loyal guests so that the business can survive and be sustainable. This study extends the literature related to the implementation of the tourist loyalty model in the hospitality and tourism industry, especially homestays in tourism villages.